Development of axis movement controller for 2-axis configuration machine control - Haidil Hazha, Husaini (2007)
This project is done to design an axis movement controller for 2-axis configuration machine control. The focus is to control the stepper motor (unipolar) inside the printer machine. The controller is design by driving the stepper motor to control the movement of conveyor on printer system. The aim of the project is to control the movement of conveyor for every 1cm per step, forward and reverse. The axis control algorithm is program in the PIC16F877 microcontroller using software PIC proBasic. This project also will present the expected performance of the 2-axis motor, construction of hardware and software development to gather the result. Finally, the result will be evaluated by comparing the system analysis with theory calculation. From the performance result, shows that stepper motor will move around 144 degree for 1 cm. In conclusion a stepper motor inside the printer system has some error in running around 0.02cm after each expected 1cm per step. -Author